Effect of NH3-flow modulation on the morphological properties of nonpolar a-plane AlGaN epilayers. (November 2021) - Nasir, Abbas; Zhang, Xiong; Zakria, M.; Zhang, Jin; Hu, Guohua; Cui, Yiping
Abstract: In this article, the effect of ammonia (NH3 ) flow-modulation on the crystalline quality and morphology of the nonpolar a- plane AlGaN epilayer grown on the r -plane sapphire substrate was reported. The as-grown metal-organic chemical vapor deposition (MOCVD) epilayers have been diagnosed with high-resolution X-ray diffraction, atomic force microscopy, and scanning electron microscopy techniques. It was found that with the introduction of proper interruption of NH3 -flow during the MOCVD growth process, enormous reduction in the threading dislocation density (TDD) and significant improvements in the crystalline quality and surface morphology could be realized. By optimizing the NH3 -flow interruption time to 30 s during the growth of the nonpolar AlGaN intermediate layer, a small root-mean-square value of 1.8 nm for the surface roughness and a TDD of 2 × 10 10 cm −2 were achieved. Moreover, the full width at half maximum values determined from the X-ray rocking curves were reduced from 2410 to 1512 arcsec and 2355 to 1645 arcsec along c- and m- plane directions, respectively. Highlights: Effect of NH3 -flow modulation on characteristics of nonpolar AlGaN epilayers have been investigated. The NH3 -flow interaction has strongly improves the crystalline quality and surface morphology. With the NH3 -flow interaction time, the FWHM reduced from 2410 to 1512 arcsec and from 2355 to 1645 arcsec along c- and m-plane directions, respectively.